1972
DOI: 10.1210/jcem-34-6-1003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Spermatogenesis and Serum Gonadotropin Levels in Azoospermia and Oligospermia

Abstract: Follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels, the sperm count and the histologic appearance of the testis were studied in 56 patients with azoospermia or oligospermia.FSH is elevated in those cases of azoospermia where gametogenesis is arrested prior to spermatid differentiation. Serum FSH is normal, however, in most patients in whom spermatids and spermatozoa are detectable on testicular biopsy. There is no relationship between the sperm count and the concentration of serum FSH.No co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
74
1
1

Year Published

1975
1975
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(88 citation statements)
references
References 7 publications
12
74
1
1
Order By: Relevance
“…Indeed, due to LH spontaneous peaks fluctuations (Legros et al, 1974) the demonstration of a preserved LH-free T (positive) relationship in normal or "sub normal" men would need serial, 10-20 min interval blood samplings and statistical methods that take into account the different half lives of the two hormones and the delay between hypophyseal LH and testicular T release. Interestingly, since plasma FSH is quite stable (Legros et al, 1974) and its level is related to the quality of the spermatogenesis (Franchimont et al, 1972) it is not too surprising that its plasma level is related to another aspect of testicular function, which is T production. Moreover, this is a negative relationship, which suggests that at least part of the androgen deficiency in ageing male might be of testicular origin, as previously suspected through the demonstration of an increased release of LRH-induced LH release as of age 50 (Legros and Bruwier, 1979) and a decreased HCG-induced testosterone release (Harman and Tsitouras, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, due to LH spontaneous peaks fluctuations (Legros et al, 1974) the demonstration of a preserved LH-free T (positive) relationship in normal or "sub normal" men would need serial, 10-20 min interval blood samplings and statistical methods that take into account the different half lives of the two hormones and the delay between hypophyseal LH and testicular T release. Interestingly, since plasma FSH is quite stable (Legros et al, 1974) and its level is related to the quality of the spermatogenesis (Franchimont et al, 1972) it is not too surprising that its plasma level is related to another aspect of testicular function, which is T production. Moreover, this is a negative relationship, which suggests that at least part of the androgen deficiency in ageing male might be of testicular origin, as previously suspected through the demonstration of an increased release of LRH-induced LH release as of age 50 (Legros and Bruwier, 1979) and a decreased HCG-induced testosterone release (Harman and Tsitouras, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the high circulating FSH concentration was probably due to a lack of a gonadal negative feedback which could be ge ne rate d fr om the ger m ce lls beyond the spermatogonia. The results of the present study suggest that a high level of circulating FSH in bovine XY females is probably due to the lack of inhibin as shown in man with azoospermia and oligospermia [2,5,9,18]. It is now beyond question that inhibin is a major factor in the regulation of FSH secretion in females.…”
Section: Discussionmentioning
confidence: 50%
“…There are cosiderable informations regarding the role of testosterone in the feedback control of LH secretion in normal males (Peterson et al, 1968;Lee et al, 1972;Sherins and Loriaux, 1973;Capell et al, 1973;Sterwart-Bentley et al, 1974) and Klinefelter's syndrome (Capell et al, 1973;Rosen and Weinstraub, 1971). However there have been controversies regarding the substances which regulate the feedback control of FSH release in normal males (Franchimont et al, 1972;Sherins and Loriaux , 1973;Lee et al, 1972;Van Thiel et al, 1972) and Klinefelter's syndrome (Capell et al, 1973;Leonard et al, 1972). All the factors about the feedback control of FSH release have not been confirmed completetly.…”
Section: Discussionmentioning
confidence: 99%
“…All the factors about the feedback control of FSH release have not been confirmed completetly. It has been reported that the substance which regulates the feedback control of FSH release is testosterone (Lee et al, 1972;Capell et al, 1973), estrogen (Sherins and Loriaux, 1973), estrogen converted from testosterone (Sterwart-Bentley et al, 1974) or other factors (Franchimont et al, 1972;Kelch et al, 1972;Van Thiel et al, 1972) in normal males. A dose of 25mg/day for 3 days of testosterone propionate was selected in this study, because the dose may be sufficient to suppress the serum LH and FSH level in normal males (Lee et al, 1972).…”
Section: Discussionmentioning
confidence: 99%